Interactive E-LKPD Based on CTL as Digital Learning Media for Advertisements, Slogans, and Posters Text Materials - Afnita; Amril Amir; Andria Catri Tamsin; Efrianto; Faiza Nurrahmah (Pascasarjana ISBI Bandung Conference Series, 2025)
Interactive e-LKPD based on CTL is an alternative learning media for advertisements, slogans, and posters text materials that can visualize picture, audio, and video to make it easier for junior high school students to understand Bahasa Indonesia learning. This research aims to develop interactive e-LKPD based on CTL as a digital media for learning advertisements, slogans, and posters text mataerials. This research uses mixed methods. The research model used is 4-D. Data was collected using questionnaires and interviews. The research results show that (1) the creation of interactive e-LKPD based on CTL follows the 4-D research model up to the stage of product validation; (2) The validation results of e-LKPD in category very valid. Therefore, interactive e-LKPD based on CTL is suitable for use as a digital learning media for advertisements, slogans, and posters text materials. Keywords: e-worksheet; contextual teaching and learning; advertisements